MAIN DIRECTIONS OF ECOLOGICAL-ORIENTED INNOVATION CONSTRUCTION AND REPAIR IN THE SPHERE OF COMMUNAL SERVICES IN THE IMPLEMENTATION OF THE RENOVATION PROGRAM IN THE CITY OF MOSCOW - E. Zimin; S. Kiseleva (Вестник университета)
The paper defines the basic directions of development of the environmental-focused innovative construction in the sphere of communal services. The negative economic and ecological aftermath of the waste disposal from dismantling of buildings on landfills are revealed. The calculations are made of the amount of secondary macadam fraction 5 to 20, which can be obtained from dismantling buildings in the course of realization of the Renovation Program in the city of Moscow and used further for production of concrete for construction of new buildings. The main tasks of improving the legal basis in the sphere of communal services are defined